Hydrothermal conversion of kaolin to kalsilite (kalSiO₄): the effect of K₂CO₃ concentrations - Eddy Mohd Farid Mohd Yusslee (Pusat e-pembelajaran, UMS, 2021)
Kaolin was used as a silica and alumina precursor in the hydrothermal synthesis of kalsilite with the addition of potassium carbonate (K₂CO₃) as a potassium source. The effects of different K₂CO₃ concentrations have been studied. After a 24-hour hydrothermal reaction at 200°C, kaolin treated with 1.25M K₂CO₃ shows 28.7°, 34.2°, and 42.3° as the most significant peaks under X-ray diffraction (XRD) which corresponds to hexagonal kalsilite. In addition, Field emission scanning electron microscopy (FESEM) images also revealed hexagonal particles proving the formation of the desired kalsilite. At K₂CO₃ concentrations less than 1.0M, boehmite and bayerite were identified to be the primary products while kalsilite forms as a minor crystalline phase. Hexagonal kalsilite was observed as the major product at higher (>1.0M) K₂CO₃ concentration while the reaction kept constant at 200°C.